PELATIHAN SHOOTING DENGAN SASARAN TETAP LEBIH EFEKTIF DARI PADA PELATIHAN SHOOTING SASARAN BERUBAH UNTUK KETEPATAN SHOOTING KE GAWANG PERMAINAN SEPAK BOLA - Klaudius H. M. Meti; J Alex Pangkahila; Oktovianus Fufu; Bagus Komang Satriyasa; Ketut Tirtayasa; Luh Made Indah Sri Handari Adiputra (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Football is part of the game that aims to put the ball into the opponent's goal. Reality on the ground observed during this time that many players do not have a good ability to do the shooting to the goal, so it needs to be a training program that aims to improve the accuracy of shooting at goal. Model training provided that training remains the target shooting and target shooting training changed. Objective: The purpose of this research, is to determine the shooting training with fixed targets and training target shooting with a change to the accuracy of shooting at goal. Method: The research is experimental with pre-test and post-test group design in Students of PJKR in PGRI University-Kupang, with a sample of 28 students, divided into two and each group is divided into 14 subjects. Group 1 was given training shooting targets fixed and group 2 was given training shooting target changes that conducted for 8 weeks with with frequency of three times in a week. Results of the research were analyzed using normality test with the Shapiro-Wilk Test and Test of Homogeneity with Leven's Test. Result: Paired t-test to determine the accuracy of shooting in mean difference in group 1 that using fixed target shooting with a mean pre-training =3.5±0.7 and the mean after training =6.7±1.0 with difference =3.2, and the percentage increase =91.42% (p<0.05). While in group 2 that using training target shooting with a mean change before training =3.3± 0.6 and the mean after training =4.6±0.6 to 1.3 and the percentage difference =39.39% increase (p<0.05). The results of the different effects goal shooting accuracy changes were tested by t-independent inter-group before and after training at the limit of significance ?=0.05. The mean change in the accuracy of shooting before training with a value of p>0.05, which means that the initial conditions are the same and after the training has a value of p<0.05. Conclusion: It can be concluded that, fixed target shooting and changed target shooting remain unchanged equally gives the effect of increased shooting accuracy (p<0.05). But the increase in group 1 that using fixed target shooting training is still better than in group 2 that using changed target shooting. Suggestion: It is advisable to use a fixed target shooting training in the process of training, the recruitment of players or athletes, because the effect is more effective.